Formica rufa ants have a limited effect on the abundance of the parasitic fly Ernestia rudis in Scots pine plantations - Véle, Adam; Dobrosavljević, Jovan (Sociobiology, 2021)
Red wood ants (the Formica rufa group) are important predators which affect animal communities in their territory. Therefore, they are useful in forest protection. On the other hand, they also prey on beneficial organisms. We have asked whether Formica rufa L. affects the abundance of the parasitic flies Ernestia rudis (Fallén). Ten anthills situated in about 40-year- old pine plantations were used for the study. The presence of E. rudis cocoons was assessed in eight soil samples excavated in the surrounding of each nest at a distance of 2–17 m. Our results show a considerably lower abundance of E. rudis only to 4.5 m from the nests. The occurrence of Formica rufa ants therefore had no significant effect on the beneficial E. rudis population in plantation forests, where ants populations are low.